2015
DOI: 10.4103/2231-0762.170524
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of iron and multivitamin drops on enamel microhardness of primary tooth

Abstract: Objectives:Iron and multivitamin drops are being frequently prescribed in children less than 2 years of age. Due to their low pH levels, these drops may lead to the softening of enamel and accelerate the destructive process. The aim of the present study was to investigate the enamel microhardness of primary teeth after exposing them to iron and multivitamin drops.Materials and Methods:Forty healthy anterior teeth were randomly divided into four groups of 10 samples each. Samples were exposed to two iron drops … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 22 publications
(26 reference statements)
0
12
0
1
Order By: Relevance
“…Concerning non- antimicrobial medication, the cariogenic effect and erosive potential of the PLM may override the cariostatic effect of the therapeutics. [29][30][31] Hence, prolonged consumption of liquid medicines poses a significant threat for good oral health. The deleterious effect of antimicrobials in syrup form containing sugars can be minimised by incorporating sugar substitutes which are called sugar free medicines (SFMs).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Concerning non- antimicrobial medication, the cariogenic effect and erosive potential of the PLM may override the cariostatic effect of the therapeutics. [29][30][31] Hence, prolonged consumption of liquid medicines poses a significant threat for good oral health. The deleterious effect of antimicrobials in syrup form containing sugars can be minimised by incorporating sugar substitutes which are called sugar free medicines (SFMs).…”
Section: Discussionmentioning
confidence: 99%
“…6,[34][35][36] Findings of plaque pH studies have also proven its cariogenic nature. [29][30][31] Frequent use of liquid medicine increases the risk of enamel caries by increasing the oral bacteria fermentation. With low pH environment, the micro-flora shifts from resident to more cariogenic one.…”
Section: Discussionmentioning
confidence: 99%
“…20 A study showed that a combination of iron drops and multi-vitamin drops can erode the enamel surface of deciduous teeth; therefore, they might increase the susceptibility of teeth to ECC. 21…”
Section: Discussionmentioning
confidence: 99%
“…They found this drugs have low pH and can reduced the average enamel microhardness of primary teeth. [ 14 ]…”
Section: Discussionmentioning
confidence: 99%